2009
DOI: 10.1016/j.brainres.2008.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of progesterone administration on infarct volume and functional deficits following permanent focal cerebral ischemia in rats

Abstract: Recent experimental evidence indicates that progesterone (PROG) protects against various models of brain injury, including ischemic stroke. Most human studies of pharmacologic treatments for acute cerebral stroke have failed despite initial success in animal models. To simulate better the typical human stroke without reperfusion, the present study was conducted to examine the efficacy of PROG on infarct volume and functional outcome in a permanent model of stroke, using direct cauterization of the middle cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
85
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 62 publications
12
85
0
Order By: Relevance
“…We selected the high P4 doses on the basis of our in vitro data and our previous reports that P4 is neuroprotective at lower doses (8 and 16 mg/kg) against traumatic brain injury and stroke (24)(25)(26). In the current experiment, we found a potent inhibitory effect of high-dose P4 on neuroblastoma tumor growth in nude In a comparative study, Wiehle et al (27) tested RU486, P4 and CDB-4124 (nor-progestin) against mammary tumors in vivo and observed that P4 treatment at 10 mg/kg for 28 days increased the size and number of tumors in female rats.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the high P4 doses on the basis of our in vitro data and our previous reports that P4 is neuroprotective at lower doses (8 and 16 mg/kg) against traumatic brain injury and stroke (24)(25)(26). In the current experiment, we found a potent inhibitory effect of high-dose P4 on neuroblastoma tumor growth in nude In a comparative study, Wiehle et al (27) tested RU486, P4 and CDB-4124 (nor-progestin) against mammary tumors in vivo and observed that P4 treatment at 10 mg/kg for 28 days increased the size and number of tumors in female rats.…”
Section: Discussionmentioning
confidence: 99%
“…PROG was dissolved in 22.5% 2-hydroxypropyl-β-cyclodextrin, and the rats received an initial intraperitoneal injection of PROG (8 mg/kg) at 1 h post-occlusion followed by subcutaneous injections at 6, 24 and 48 h (13,14). In the vehicle-treated group, PROG was replaced by 2-hydroxypropyl-β-cyclodextrin in the same volume.…”
Section: Methodsmentioning
confidence: 99%
“…PROG has been shown to display neuroprotective properties following cerebral ischemia, decreasing lesion volume and improving functional recovery (14,19,13). Both cell survival and neuronal density are improved by acute or chronic PROG treatment in male (19) and female (20) animals.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] Progesterone has already been shown to be safe and effective for several clinical applications, e.g., hormone replacement therapy, and a variety of preparations are available for different modes of administration. 15 Furthermore, no severe adverse effects have been reported even when progesterone was used at high dose.…”
Section: Introductionmentioning
confidence: 99%